Slick Potassium Channels Control Pain and Itch in Distinct Populations of Sensory and Spinal Neurons in Mice. (18th March 2022) - Flauaus, Cathrin; Engel, Patrick; Zhou, Fangyuan; Petersen, Jonas; Ruth, Peter; Lukowski, Robert; Schmidtko, Achim; Lu, Ruirui
Abstract : Background: Slick, a sodium-activated potassium channel, has been recently identified in somatosensory pathways, but its functional role is poorly understood. The authors of this study hypothesized that Slick is involved in processing sensations of pain and itch. Methods: Immunostaining, in situ hybridization, Western blot, and real-time quantitative reverse transcription polymerase chain reaction were used to investigate the expression of Slick in dorsal root ganglia and the spinal cord. Mice lacking Slick globally (Slick –/– ) or conditionally in neurons of the spinal dorsal horn (Lbx1-Slick –/– ) were assessed in behavioral models. Results: The authors found Slick to be enriched in nociceptive Aδ-fibers and in populations of interneurons in the spinal dorsal horn. Slick –/– mice, but not Lbx1-Slick –/– mice, showed enhanced responses to noxious heat in the hot plate and tail-immersion tests. Both Slick –/– and Lbx1-Slick –/– mice demonstrated prolonged paw licking after capsaicin injection (mean ± SD, 45.6 ± 30.1 s [95% CI, 19.8 to 71.4]; and 13.1 ± 16.1 s [95% CI, 1.8 to 28.0]; P = 0.006 [Slick –/– {n = 8} and wild-type {n = 7}, respectively]), which was paralleled by increased phosphorylation of the neuronal activity marker extracellular signal–regulated kinase in the spinal cord. In the spinal dorsal horn, Slick is colocalized with somatostatin receptor 2 (SSTR2), and intrathecal preadministration of the SSTR2 antagonist CYN-154806 prevented increased capsaicin-induced licking in Slick –/– and Lbx1-Slick –/– mice. Moreover, scratching after intrathecal delivery of the somatostatin analog octreotide was considerably reduced in Slick –/– and Lbx1-Slick –/– mice (Slick –/– [n = 8]: 6.1 ± 6.7 bouts [95% CI, 0.6 to 11.7]; wild-type [n =8]: 47.4 ± 51.1 bouts [95% CI, 4.8 to 90.2]; P = 0.039). Conclusions: Slick expressed in a subset of sensory neurons modulates heat-induced pain, while Slick expressed in spinal cord interneurons inhibits capsaicin-induced pain but facilitates somatostatin-induced itch. Abstract : Using male and female mouse models, it was observed that Slick reduces responses to noxious thermal and chemical stimulation. Conversely, Slick expressed on spinal interneurons facilitates somatostatin-induced itch. Analgesics targeting Slick channels may decrease pain but could increase itching if they reach the central nervous system.